let T be TopSpace; :: thesis: for A being Subset of T holds
( A is condensed iff ex B being Subset of T st
( B is regular_open & B c= A & A c= Cl B ) )

let A be Subset of T; :: thesis: ( A is condensed iff ex B being Subset of T st
( B is regular_open & B c= A & A c= Cl B ) )

thus ( A is condensed implies ex B being Subset of T st
( B is regular_open & B c= A & A c= Cl B ) ) :: thesis: ( ex B being Subset of T st
( B is regular_open & B c= A & A c= Cl B ) implies A is condensed )
proof
assume A1: A is condensed ; :: thesis: ex B being Subset of T st
( B is regular_open & B c= A & A c= Cl B )

then A2: Cl (Int A) = Cl A ;
take Int (Cl A) ; :: thesis: ( Int (Cl A) is regular_open & Int (Cl A) c= A & A c= Cl (Int (Cl A)) )
Int (Cl A) = Int A by A1;
hence ( Int (Cl A) is regular_open & Int (Cl A) c= A & A c= Cl (Int (Cl A)) ) by ; :: thesis: verum
end;
given B being Subset of T such that A3: B is regular_open and
A4: B c= A and
A5: A c= Cl B ; :: thesis: A is condensed
A6: Int (Cl B) = B by ;
Int B c= Int A by ;
then A7: Cl (Int B) c= Cl (Int A) by PRE_TOPC:19;
A8: Cl (Int B) = Cl B by ;
Int A c= Int (Cl B) by ;
then Cl (Int A) c= Cl B by ;
then A9: Cl B = Cl (Int A) by ;
Cl B c= Cl A by ;
then A10: Int (Cl B) c= Int (Cl A) by TOPS_1:19;
Cl A c= Cl (Cl B) by ;
then Int (Cl A) c= Int (Cl (Cl B)) by TOPS_1:19;
then B = Int (Cl A) by ;
hence A is condensed by A4, A5, A9, Th10; :: thesis: verum